How do earthworms affect organic matter decomposition in the presence of clay-sized minerals?. (April 2020) - Barthod, J.; Dignac, M.-F.; Le Mer, G.; Bottinelli, N.; Watteau, F.; Kögel-Knabner, I.; Rumpel, C.
Abstract: Clay-sized soil minerals are known to protect organic carbon (OC) from mineralisation by formation of organo-mineral associations limiting its availability to microorganisms. The impact of soil fauna on these processes is poorly known. The aim of this study was to investigate the effect of earthworms on organic matter (OM) decomposition and association with minerals during a laboratory experiment. We used a model system consisting of fresh OM incubated with and without epigeic earthworms ( Eisenia andrei and foetida ) in presence of different types and amounts of phyllosilicates (kaolinite, montmorillonite) and an iron oxide (goethite) and combinations of these minerals. Our experimental setup included a high OM:mineral ratio to represent the soil-litter interphase. We monitored OC mineralisation during 196 days. Additionally, we investigated physicochemical parameters and chemical OM characteristics of decomposition products by determination of water-soluble OC (WSOC) and acquisition of solid-state 13 C NMR spectra. We also analysed microscale organisation of the organo-mineral associations produced with and without earthworms by transmission electron microscopy (TEM). Earthworms enhanced OC mineralisation in all treatments. They also led to greater reductions of OC emissions in the presence of minerals as compared to the mineral-free control, depending on the type and amount of minerals added. The presence of earthworms affected microbial biomass, the concentration of WSOC and increased the contribution of aromatic compounds to OM decomposition products. Microscale analyses by TEM showed that earthworms favoured association of minerals with partly degraded OM along with completely degraded material, while in absence of earthworms only completely degraded OM was associated with minerals. We conclude that earthworms impact OM decomposition through (1) their effect on microbial biomass and the physicochemical parameters of microbial habitat and (2) the formation of OM associations by changing the OM types associated to minerals and possibly by creating closer association of partly degraded OM and iron oxides. The stability of these associations remains to be investigated. Highlights: Earthworms increase organic carbon mineralisation in presence of minerals. Earthworms strengthen stabilising effect of minerals. Earthworm impact on physicochemical soil parameters depends on mineral type. Earthworms influence organic matter types associated to soil minerals.